2016
DOI: 10.1590/s0100-736x2016000400001
|View full text |Cite
|
Sign up to set email alerts
|

Virulence profiles of enterotoxigenic Escherichia coli isolated from piglets with post-weaning diarrhea and classification according to fecal consistency

Abstract: The aim of this study was to assess the frequency and association of virulence factors of Escherichia (E.) coli isolated from weaned piglets with diarrhea and to correlate it with fecal consistency. A total of 152 rectal swabs were collected from 25-40 day-old piglets with diarrhea, in farms of Southern Brazil. Phenotypical and molecular techniques were used for bacterial isolation, characterization and classification of enterotoxigenic E. coli (ETEC) pathotypes. Statistical analysis was carried out to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
10
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 14 publications
7
10
2
1
Order By: Relevance
“…Pathogenic strains of ETEC adhere to enterocytes and produce enterotoxins and therefore require the expression of at least one fimbria and one toxin [ 5 ]. The present study revealed that 40% of the analyzed samples presented pathogenic ETEC, similar to previous reports of 54.8% and 50.5% occurrence [ 14 23 ]. However, expression of a toxin gene with no fimbrial gene expression was observed in 13.6% (18/132) of the samples in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Pathogenic strains of ETEC adhere to enterocytes and produce enterotoxins and therefore require the expression of at least one fimbria and one toxin [ 5 ]. The present study revealed that 40% of the analyzed samples presented pathogenic ETEC, similar to previous reports of 54.8% and 50.5% occurrence [ 14 23 ]. However, expression of a toxin gene with no fimbrial gene expression was observed in 13.6% (18/132) of the samples in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Although this value was less than the 94.8% and 92% reported by other authors using cultivated bacterial assessment [ 21 25 ], the results obtained through the extraction from paraffin-embedded tissues were similar to the previously reported 77% based on isolated E. coli assessment [ 26 ], and is greater than the 29.2%, 42%, and 62.9% based on multiplex PCR [ 14 17 23 ]. The frequencies of virulence genes observed in the present study were similar to those in previous reports in which the virulence types for F18 and F4 fimbriae and for STaP and STb toxins were most frequent in cultivated bacteria [ 6 14 21 23 25 ]. The occurrence of high frequencies of F18 and F4 fimbrial genes may be explained by the fact that 53% of the samples were from weaning pigs, which is similar to that in a previous study that evaluated post-weaning E. coli isolates via multiplex PCR [ 26 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, among EPEC isolated from children in Brazil, only 25% indicated the ability of hemolysin production [38] that was lower than the rate we obtained here in this study. Additionally, the rate of hemolysin activity in our ETEC isolates was close to the similar isolates from diarrhea patients in Iran and Brazil [35,39]. The high prevalence of hemolysin activity in DEC isolates suggests its role in the increased pathogenicity of these strains.…”
Section: Discussionsupporting
confidence: 76%